2019
DOI: 10.1016/j.est.2019.100761
|View full text |Cite
|
Sign up to set email alerts
|

An insight into the errors and uncertainty of the lithium-ion battery characterisation experiments

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 23 publications
(26 reference statements)
0
14
0
Order By: Relevance
“…Fourth, the torque on the connections must be carefully controlled and kept constant. Taylor et al [13] found the optimal torque to be 12.5 Nm for their connectors. If possible, all cells belonging to one set of experiments should be tested on the same machine and in the same temperature chamber if temperature is not a variable.…”
Section: Test Preparationmentioning
confidence: 99%
See 4 more Smart Citations
“…Fourth, the torque on the connections must be carefully controlled and kept constant. Taylor et al [13] found the optimal torque to be 12.5 Nm for their connectors. If possible, all cells belonging to one set of experiments should be tested on the same machine and in the same temperature chamber if temperature is not a variable.…”
Section: Test Preparationmentioning
confidence: 99%
“…A recent study by Taylor et al [13] showed that, without careful consideration, slight differences in the experimental setup could induce up to 4% difference in experimental results on similar cells. This error has environmental and procedural origins [13].…”
Section: Test Preparationmentioning
confidence: 99%
See 3 more Smart Citations